2015
DOI: 10.3390/agronomy5030418
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Aluminium Accumulation and Resistance between Genotypes of the Genus Fagopyrum

Abstract: Aluminium (Al) toxicity is a major factor reducing crop productivity worldwide. There is a broad variation in intra-and inter-specific Al resistance. Whereas the Al resistance mechanisms have generally been well explored in Al-excluding plant species, Al resistance through Al accumulation and Al tolerance is not yet well understood. Therefore, a set of 94 genotypes from three Fagopyrum species with special emphasis on F. esculentum Moench were screened, with the objective of identifying genotypes with greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The genetic variability could affect the growth of the plants and their susceptibility when transferred from a soil substrate to hydroponic condition. The potential impact of genetic variability on plants growing in hydroponics has been reported for Sorghum bicolor and Fagopyrum esculentum (Jordan et al , 1979; Klug et al , 2015), but may not explain the subsequent death of the –Al plants. Furthermore, earlier growth conditions between our seedlings and saplings differed, as the saplings were grown in a greenhouse, experiencing mild winter temperatures in contrast to the seedlings, which were germinated at ambient winter temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic variability could affect the growth of the plants and their susceptibility when transferred from a soil substrate to hydroponic condition. The potential impact of genetic variability on plants growing in hydroponics has been reported for Sorghum bicolor and Fagopyrum esculentum (Jordan et al , 1979; Klug et al , 2015), but may not explain the subsequent death of the –Al plants. Furthermore, earlier growth conditions between our seedlings and saplings differed, as the saplings were grown in a greenhouse, experiencing mild winter temperatures in contrast to the seedlings, which were germinated at ambient winter temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Although the chemical form in which Al is taken up by the plant is unknown, the primary uptake mechanism appears to be transport via the transpiration stream, as the highest concentrations were observed in the leaves of the plants. The most commonly reported forms of Al complexes detected in the xylem sap of Al accumulators are Al citrate, malate, oxalate and fluorine, as these molecules are known to have a strong binding affinity to Al (Watanabe and Osaki, 2001; Flaten, 2002; Morita et al , 2004; Satoh, 2006; Klug et al , 2015). The root represents the only organ that is directly in contact with soluble Al, explaining the high concentrations within the root tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Fagopyrum including common buckwheat ( Fagopyrum esculentum ), tartary buckwheat ( Fagopyrum tataricum ) and wild buckwheat ( Fagopyrum homotropicum ) shows high tolerance to aluminium (Al) ion toxicity and accumulates high Al in the leaves without showing any toxicity symptoms (Ma et al ., ; Klug et al ., ; Wang et al ., ). Physiological studies have revealed that both external and internal detoxification mechanisms are involved in high Al tolerance in buckwheat (Ma et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic variation in plant sensitivity has been well documented, but mechanisms for resistance remain under investigation [18,19]. Roots are an important target for Al-induced damage, and inhibition of root growth occurs rapidly in response to exposure of the root tip to aluminum [17,20].…”
Section: Border Cell Trapping Of Aluminummentioning
confidence: 99%